The 2011 PHARMINE report on pharmacy and pharmacy education in the European Union - Atkinson J; Rombaut B (Centro de Investigaciones y Publicaciones Farmaceuticas, 2011)
The PHARMINE consortium consists of 50 universities from European Union member states or other European countries that are members of the European Association of Faculties of Pharmacy (EAFP). EU partner associations representing community (PGEU), hospital (EAHP) and industrial pharmacy (EIPG), together with the European Pharmacy Students' Association (EPSA) are also part of the consortium. The consortium surveyed pharmacies and pharmacists in different settings: community, hospital, industry and other sectors. The consortium also looked at how European Union higher education institutions and courses are organised.The PHARMINE survey of pharmacy and pharmacy education in Europe produced country profiles with extensive information for EU member states and several other European countries. These data are available at: http://www.pharmine.org/losse_paginas/Country_Profiles/. This 2011 PHARMINE report presents the project and data, and some preliminary analysis on the basic question of how pharmacy education is adapted to pharmacy practice in the EU.